2013
DOI: 10.1182/blood-2012-08-448977
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived CMV-specific T cells reduce the requirement for CMV-directed pharmacotherapy after allogeneic stem cell transplantation

Abstract: Key Points• Infusion of CMV-specific T cells early posttransplant does not increase acute or chronic graft-versus-host disease.• CMV-specific T cells early posttransplant reduce the need for pharmacotherapy without increased rates of CMV-related organ damage.We investigated the use of adoptively transferred donor-derived cytomegalovirus (CMV) specific cytotoxic T lymphocytes (CTL) as immune reconstitution postallogeneic transplant in a phase 2 study. Fifty patients were infused with a single dose of 2 3 10 7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
152
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 33 publications
8
152
0
1
Order By: Relevance
“…Recent clinical studies have shown that infusion of CMVspecific T cells early posttransplant does not appear to increase GVHD, but reduces the requirement for CMV-directed pharmacotherapy. 11 Our adoptive transfer studies in a controlled model system support these findings and demonstrate that there is no difference in the efficacy of antiviral CD8…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Recent clinical studies have shown that infusion of CMVspecific T cells early posttransplant does not appear to increase GVHD, but reduces the requirement for CMV-directed pharmacotherapy. 11 Our adoptive transfer studies in a controlled model system support these findings and demonstrate that there is no difference in the efficacy of antiviral CD8…”
supporting
confidence: 73%
“…Indeed, CMV-specific CD8 1 T cells can be expanded in vitro and adoptively transferred to treat established CMV disease refractory to antiviral therapy, [15][16][17] or to reduce the need for antiviral pharmacotherapy. 11 Although this approach confirms the ability of appropriately activated T cells to limit viral replication, the cellular networks controlling virus after transplantation are poorly understood. In addition, it is clear that in the presence of GVHD, the ability to control CMV is dramatically inhibited, 5 but the relevant mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most significative experience on HSCT patients who received donor CMV-VSTCs and compared with a control group was reported in 2013 [96]. The endpoint was to evaluate if prophylaxis with CMVspecific T cells could provide short-and long-term protection against CMV infection.…”
Section: Ex Vivo Culturementioning
confidence: 99%